Penerapan Struktural Analisis Sintetik (SAS) dalam Peningkatan Keterampilan Menulis 汉字 (hànzì) Siswa Kelas XI MAS An-Nuriyah Bontocini Jeneponto - Nurwahyuni Nurwahyuni; Misnawaty Usman; Burhanuddin Burhanuddin (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2022)
Nurwahyuni, 2021. "Application of Structural Synthetic Analysis (SAS) in Improving Writing Skills for Class XI Students at MAS An-Nuriyah Bontocini Jeneponto". Thesis . Mandarin Education Study Program. Department of Foreign Language Education. Faculty of Languages and Letters. Makassar State University (supervised by Misnawaty Usman and Burhanuddin). This study aims to improve the writing skills of (hànzì) Class XI students at MAS An-Nuriyah Bontocini Jeneponto through the application of Structural Synthetic Analysis (SAS). The sample of this study was the 22 students of class XI MIA II MAS An-Nuriyah Bontocini Jeneponto. This research is a classroom action research which consists of two cycles. This research data consists of two types, namely: qualitative data and quantitative data. Qualitative data was obtained through observation while quantitative data was obtained through writing skills tests in cycle I and cycle II. The results showed that the writing skill (hànzì) with the average score of the writing skill test (hànzì) obtained by students from 63.72% with the poor category in the first cycle increased to 77% with the good category in the second cycle. These results indicate that the application of Structural Synthetic Analysis (SAS) can improve the writing skills of (hànzì) Class XI students at MAS An-Nuriyah Bontocini Jeneponto.Keywords: Synthetic Structural Analysis (SAS), Writing Skills, (hànzì), Bahasa Mandarin